رائية ابن المزجَّد في النصح والإرشاد - الصادق, ذهب (جامعة الوادي university of eloued, 2023)
ملخص: هذا البحث تحقيق مخطوط للعلاّمة ابن المزجَّد (930ه) الشافعي, في الأخلاق والآداب, مع الخالق ومع المخلوق؛ حيث تنوّعت أبياته بين الترغيب في الأخلاق الحميدة, والترهيب من الأخلاق المذمومة. وقد قسّمت البحث إلى ثلاثة مطالب, خصّصت المطلب الأول للتعريف بالناظم؛ شهاب الدّين ابن المزجَّد, فذكرت حياته الشخصيّة, والعلميّة, وتناولت في المطلب الثاني للتّعريف بالنّظم؛ مبيّنا نسبة المخطوط وتسميته, ثم موضوعه, وبعدها وصف شامل للمخطوط, والعمل الذي قمت به في تحقيقه, وفي المطلب الثالث تحقيق نصّ المخطوط. Abstract : This research is a written investigation of the scholar Ibn al-Mozjjad (930 Hijri) Al-Shafi’i, in morals and manners, with the Creator and the creature; Where his verses varied between calling out for good manners, and intimidation of the unwanted morals. This research is devided into three sections, allocating the first requirement to introduce the organizer; Shihab al-Din Ibn al-Mozajjad, where I mentioned his personal and scientific life, in the second part, I have dealt with the introduction of the his scientific system ; Indicating the proportion of the manuscript and its name, then its subject, and then a comprehensive description of the manuscript, and the work that I did in its realization, and in the third part the achievement of the written manuscript
مقال
Keywords: رائيّة؛ المزَجَّد؛ الإرشاد